The Roles of TRIMs in Antiviral Innate Immune Signaling - Shen, Zhou; Wei, Lin; Yu, Zhi-bo; Yao, Zhi-yan; Cheng, Jing; Wang, Yu-tong; Song, Xiao-tian; Li, Miao (Frontiers in Cellular and Infection Microbiology, 2021)
The Tripartite motif (TRIM) protein family, which contains over 80 members in human sapiens, is the largest subfamily of the RING-type E3 ubiquitin ligase family. It is implicated in regulating various cellular functions, including cell cycle process, autophagy, and immune response. The dysfunction of TRIMs may lead to numerous diseases, such as systemic lupus erythematosus (SLE). Lots of studies in recent years have demonstrated that many TRIM proteins exert antiviral roles. TRIM proteins could affect viral replication by regulating the signaling pathways of antiviral innate immune responses. Besides, TRIM proteins can directly target viral components, which can lead to the degradation or functional inhibition of viral protein through degradative or non-degradative mechanisms and consequently interrupt the viral lifecycle. However, new evidence suggests that some viruses may manipulate TRIM proteins for their replication. Here, we summarize the latest discoveries on the interactions between TRIM protein and virus, especially TRIM proteins' role in the signaling pathway of antiviral innate immune response and the direct "game" between them.